Surface roughness characterization on p20 tool steel in wirecut electrical discharge machining (wedm) process - Zaidatul Syima, Zainal (2013)
Wire Electrical Discharge Machining (WEDM) is one of the earliest non-traditional machining processes and has a capability in producing high precision parts. An inappropriate WEDM machining parameter will affects the efficiency of WEDM machining process and the quality of the surface roughness parts because of increasing probability on wire breakage. Therefore, this research was conducted to investigate the effect of WEDM machining parameters on surface roughness of tool steel material for injection molding. In this experiment, mold of AISI P20 hardenable steel were produced using WEDM. In material preparation phase, the raw material will undergo milling and deburring processes. The voltage, machined feed rate and wire speed were manipulated to find the best combination of WEDM machining parameters. The results show that the surface roughness values increased with increasing of voltage and it’s create higher energy on machining zones and create deeper and wider crates on machined surface. A smoother surface can be achieved by lowering the machine feed rate speed and wire speed can be ignored since it not affected on the microstructure of machined surface. As the conclusion machining process can work efficiently by controlling the machining parameters at an optimal value to avoid the risk of wire breakage when the machining process is being carried out onto a workpiece.